1994
DOI: 10.1007/bf00040587
|View full text |Cite
|
Sign up to set email alerts
|

The presequence of the precursor to the nucleus-encoded 30 kDa protein of photosystem II in Euglena gracilis Z includes two hydrophobic domains

Abstract: A cDNA clone for the extrinsic 30 kDa protein (OEC30) of photosystem II in Euglena gracilis Z was isolated and characterized. The open reading frame of the cDNA encoded a polypeptide of 338 amino acids, which consisted of a long presequence of 93 amino acids and a mature polypeptide of 245 amino acids. Two hydrophobic domains were identified in the presequence, in contrast to the presence of a single hydrophobic domain in the presequence of the corresponding proteins from higher plants. At the N- and C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…We independently sequenced and determined a complete cDNA for the preOEC30. The previously published preOEC30 lacks 46 amino acids from the N-terminus corresponding to the N-terminal signal peptide domain (19). We compared the presequences of Euglena preOEC30 and the preOEC33s from higher plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We independently sequenced and determined a complete cDNA for the preOEC30. The previously published preOEC30 lacks 46 amino acids from the N-terminus corresponding to the N-terminal signal peptide domain (19). We compared the presequences of Euglena preOEC30 and the preOEC33s from higher plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We performed heterologous import experiments using isolated chloroplasts from spinach and previously obtained Euglena truncated preOEC30 (Euglena T-preOEC30), which lacks N-terminal signal peptide domain (19). We demonstrated that the Euglena T-preOEC30 having the stroma targeting domain and thylakoid transfer domain can be imported into spinach chloroplasts.…”
mentioning
confidence: 96%
“…In both cases, plastid proteins are targeted through the endomembrane system (49,53,67,70,71). From studies of several complete, publicly available Euglena gracilis plastid protein sequences (13,25,27,28,38,44,52,56,61,64,66,73), it was predicted that the plastid proteins have an N-terminal signal sequence, an inference that was confirmed by both in vitro (38) and in vivo (70,71) experimental approaches. Following the signal sequence is the predicted transit peptide, which is sufficient for translocation across plant chloroplast membranes (29), and a hydrophobic region that acts as a "stoptransfer" sequence to prevent complete transport into the ER, such that the mature protein remains in the cytoplasm (69).…”
mentioning
confidence: 97%
“…The class I presequences were previously identified in a number of Euglena chloroplast protein precursors including but not limited to polyprotein precursors (Chan et al 1990;Henze et al 1995;Houlne and Schantz 1987;Kishore et al 1993;Lin et al 1994;Plaumann et al 1997;Santillan Torres et al 2003;Sharif et al 1989;Shigemori et al 1994;Vacula et al 1999). The class I presequence has an N-terminal presequence composed of a predicted signal peptide, for targeting to the ER ( Fig.…”
Section: The Euglena Plastid Targeting Presequence Structure; Two-clamentioning
confidence: 94%
“…Early sequencing efforts of Euglena genes encoding a number of plastid-targeted proteins identified a large bipartite presequence composed of an N-terminal domain having characteristics of a signal peptide that mediates co-translational import into the ER and a second domain having features resembling a transit peptide that mediates import into chloroplasts (Chan et al 1990;Henze et al 1995;Houlne and Schantz 1987;Kishore et al 1993;Lin et al 1994;Plaumann et al 1997;Santillan Torres et al 2003;Sharif et al 1989;Shigemori et al 1994;Vacula et al 1999). Considering the evidence, the absence of ribosomes on the outer plastid envelope membrane, the immunogold localization of LHCPII to the Golgi apparatus and the presence of a N-terminal presequence signal peptide provided compelling evidence for co-translational transport of chloroplast protein precursors into the ER, vesicular transport from the ER to the Golgi apparatus and then from the Golgi apparatus to the chloroplast for subsequent translocation through the plastid envelope into the plastid.…”
Section: Introductionmentioning
confidence: 98%